Penyuluhan Pola Makan Yang Sehat Pada Pengemudi Ojek Online Untuk Mencegah Gastritis - Antin Trilaksmi; Diani Nazma; Lira Panduwaty; Noviani Prasetyaningsih (CV. Multi Kreasi Media, 2023)
Nutritional problems do not only occur in children, but can also occur in adults. Malnutrition at productive age will have an impact on decreasing work productivity. Gastritis often arises due to lifestyle influences, including poor diet. The job of being an online motorcycle taxi driver allows unhealthy eating patterns to occur due to uncertain income and time to get passengers. This diet increases the risk for gastritis. So far no studies or counseling activities have been found, especially regarding knowledge about healthy eating patterns to prevent gastritis in online motorcycle taxi drivers, so we think it is necessary to hold health service activities in the form of education about the importance of a healthy diet. The activity was held on Saturday, November 12 2022 at the Trisakti University Faculty of Medicine attended by 30 online motorcycle taxi drivers in the West Jakarta area. This activity resulted in an increase in participants' knowledge about the importance of a healthy diet to prevent gastritis as evidenced by an increase in post-test scores after attending counseling. the conclusion of the activity is that the activity is running well supported by all related parties starting from the institutions, the implementing team and partners who are actively participating. Our advice is to periodically evaluate dietary changes after receiving counseling.